A novel approach of Consensus-based Finite-time Distributed Sliding Mode Control for Stewart platform manipulators motion tracking - Duc Cuong Vu; Tung Lam Nguyen; Danh Huy Nguyen (Results in Engineering)
The Gough-Stewart Platform, often referred to simply as the Stewart Platform, is a parallel mechanical system with six degrees of freedom, which is widely employed in simulation and precise applications. This study gives a thorough Lagrangian-based model of the Stewart Platform, emphasizing its dynamic behavior and control mechanisms. A novel distributed control technique based on Finite-time Distributed Sliding Mode Control (DSMC) is presented to establish second-order consensus in a multi-agent framework in which each leg of the platform is viewed as an autonomous agent. The control approach ensures accurate monitoring of reference trajectories. Simulations are used to validate the efficacy of the proposed control scheme by comparing it to typical decentralized PD control methods. The results simulated based on the Quasi-Physical Model show that consensus-based control outperforms the counterpart control approaches in terms of accuracy and stability.